STRATEGI PERENCANAAN PENGEMBANGAN DESA WISATA PESISIR “PESONA BAHARI” GISIK CEMANDI - Eka Dian Savitri; Hermanto Hermanto; Ratna Rintaningrum; Saifulloh Saifulloh; Dyah Satya Yoga (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
To ensure that the concept of service is in accordance with the community's needs, community service activities should begin with a needs assessment and a well-thought-out strategy. The goal of this research is to present an analysis and strategy for the development of the